“Monstro devorador do gênio”: confrontos entre imprensa e intelectuais brasileiros na pasagem do século - Silva, Maurício (Diálogos Latinoamericanos, 2010)
This article analyzes the Brazilian cultural context during the late nineteenth to the twentieth century, from a literary comparativism perspective. For this, emphasizes the author's professionalization and its relationship with journalism. This paper seeks to address the main literary tendencies of Brazil in the turn of the century, through the analysis of aesthetic characteristics present in some of its main representatives. Finally, observes the clashes between the press and Brazilian intellectuals in this period.